Direct Hospitalization Cost of Chronic Obstructive Pulmonary Disease (COPD): A Systematic Review - Desty Yuanda; Dwi Endarti; Diah Ayu Puspandari (Jurnal Multidisiplin Sahombu, 2026)
COPD is the third leading cause of death worldwide, causing 3.23 million deaths in 2019. COPD is also the 4th leading cause of death in the USA. Smoking accounts for more than 70% of COPD cases in high-income countries. COPD is a health problem with severe economic and social consequences and causes a burden of direct and indirect costs for outpatients. Direct costs include medication costs, diagnostic utility costs, disease management and follow-up costs as well as hospitalization and emergency costs. Searches were performed in PubMed, SCOPUS, and the Google Scholar databases for cost-related research on COPD published in English from 2015 to 2023. The criteria for inclusion involved identifying documented disease costs, economic impact, medical care expenditures for COPD, along with the methodology, data sources, and variables examined. COPD leads to significant expenses within the healthcare system, primarily linked to the disease's moderate to severe stages, exacerbations, and associated complications. Strengthening healthcare systems through monitoring, assessment, and health education models is crucial. These approaches aim to help patients maintain stability, preventing deterioration and subsequent hospital admissions.